Strategies to Prevent Restenosis After Drug-Coated Balloon Angioplasty - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
Despite advances in drug-coated balloon (DCB) technology, restenosis remains a persistent challenge in percutaneous coronary intervention (PCI). At Bethsaida Hospital in Indonesia, chaired by Prof. Dasaad Mulijono, we’ve reduced restenosis rates from 10–20% to just 2% through an integrated approach that combines precise lesion preparation, imagingguided intervention, and a groundbreaking lifestyle strategy: the plantbased diet (PBD). This review challenges the conventional, drug-heavy paradigm by highlighting PBD as a potent, non-pharmacological tool for combating atherosclerosis and restenosis. Backed by mechanistic insights—ranging from nitric oxide (NO)-mediated vasodilation to gut microbiome modulation—PBD offers profound cardiovascular protection while enhancing glycaemic control, blood pressure, lipid profiles, and overall metabolic health. Moreover, our centre’s deployment of artificial intelligence (AI) has revolutionized patient education and dietary adherence, accelerating realworld outcomes. Our data show that combining AI-driven personalization with lifestyle medicine is feasible and transformative. It’s time to disrupt the status quo in cardiology. This review calls for a bold paradigm shift: integrate cutting-edge interventional techniques with evidence-based nutrition and digital innovation to redefine restenosis prevention and reshape the future of cardiovascular care.